REAKSI PASAR MODAL INDONESIA TERHADAP PEMILU LEGISLATIF 2014 PADA INDEKS LQ45 DI BEI - Santoso, Heri; Sri Artini, Luh Gede (E-Jurnal Manajemen, 2015)
This study aimed to find the significant difference of abnormal return in stock Index LQ45 before and after the legislative election in 2014. This study used saturation sampling from stock index LQ45 that was registered during the period from February to July 2014. The data analysis technique used was a different test in pairs, and the window periods used were 7 days before and 7 days after the course of legislative election in 2014. The results of this study found that there was no significant difference before and after the legislative election. Based on the results, it is shown that market was not in the form of half-strong market in terms of information, which means it did not react toward the occurrence of legislative election in 2014, as the investors had predicted that the results of Legislative Election 2014 were not much different from the information obtained from the survey agency which was conducted prior to Legislative Election 2014.
Keywords: abnormal return, event study, legislative election